Undercover Jeopardy - Tailer, Kathleen
"Taken hostage in a bank robbery, the last person Detective Daniel Morley expects to find disguised as a robber is his ex-fiancée, FBI agent Bethany Walker. Now, with a mole in law enforcement putting Bethany's life in danger, Daniel must join her undercover to protect her. But can this pretend couple confront the issues that ended their real relationship...and stay alive to claim a future together?" -- Page [4] cover.